Task Delegation Practices and Challenges Encountered by the School Heads in Public Schools (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the effectiveness of task delegation practices and the challenges encountered by school heads, with the aim of identifying factors that influence leadership efficiency and operational outcomes in public schools. Specifically, the research sought to determine the effectiveness of task delegation practices, the nature of challenges experienced by school heads, and whether these practices and challenges significantly vary according to demographic characteristics such as sex, age, position, years in service, and highest educational attainment. The study addressed a research gap on the interplay between delegation effectiveness and operational challenges in school leadership, particularly in the context of schools with experienced administrators holding advanced degrees. Data were collected from school heads using structured questionnaires and analyzed using descriptive and inferential statistics to explore patterns, differences, and relationships between delegation practices and encountered challenges.Findings showed that school heads generally practiced effective task delegation but faced challenges like communication gaps, trust issues, unclear roles, and limited training. Delegation effectiveness and challenges varied by demographics such as years of service and educational attainment, underscoring the role of experience and qualifications. However, no direct link was found between effectiveness and challenges, indicating that strong practices alone may not resolve operational difficulties. To address this, recommendations and a program proposal were developed to improve clarity, trust, competence, monitoring, and professional development. These measures aim to strengthen delegation, reduce inefficiencies, and enhance performance. Future research may broaden scope and sample to refine results.